Science and magic in the modern world - Subbotskiĭ, E. V. (Evgeniĭ Vasilʹevich), author.
1 online resource
Keywords: Science and Magic in the Modern World is a unique text that explores the role of magical thinking in everyday life. It provides an excellent psychological look at the subconscious belief in magic in both popular culture and society, as well as experimental research that considers human consciousness as a derivative of belief in the supernatural, thus showing that our feelings, emotions, attitudes and other psychological processes follow the laws of magic. This book synthesises the science of natural' phenomena and the magic of the supernatural' to present an interesting look at the juxtaposition of the inner and outer selves. Fusing research into psychological disorders, subconscious feelings, as well as the rising presence of artificial intelligence, this book demonstrates how an engagement with magical thinking can enhance one's creativity and cognitive skills. Science and Magic in the Modern World is an invaluable resource for those studying consciousness, as well as those looking at the effect of magical thinking on religion, politics, science and society.